CASE STUDIES OF USE OF DESIGN OF EXPERIMENTS IN MATERIAL RESEARCH - Salil Kumar Roy; I Nyoman Sutapa (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2003)
The paper describes principles of factorial and fractional factorial design of experiments. The various ways of analysing data obtained by these procedures are shown via four case studies. Yates method was followed in case 1 where the effect of anode type, carbon content of steel, temperature, and agitation on cathodic protection of steel in seawater, on current density, was studied. In case 2, a glass was formulated within 10 constituante melted, quantity water and tested for flow caracteristics, from the result the factor effect was calculated. In case 3, analysis of results is done in a very simple way. In this case, the effect of carbon content, surface condition, temperature, and agitation on the corrosion of steel in seawater was studied. In case 4, the effect of eleven constituents on acid resistance of a cast iron enamel has been studied through sixteen experimental compositions. This case gives a method to find out which of the sixteen experimental compositions is nearest to a target value.